IDENTIFICATION AND IN SILICO CHARACTERIZATION OF TaGSTU30 AND TaTPS1 GENES IN BREAD WHEAT - AMARDEEP*; T. SINGH (The Journal of Research ANGRAU, 2023)
In case of rice, OsGSTU30 and OsTPS1 genes play a critical role in development, metabolism, and abiotic stress responses.In the study, it was aimed to identify and characterizeOsGSTU30 and OsTPS1genes in wheat reference genomic data. Functional domains, physicochemical properties and subcellular localization of both genes were identified. The homology modeling method was used to predict the 3D structures and Ramachandran plots were also predicted to evaluate protein structures. In silico expression profiles of wheat,TaGSTU30 and TPS1 genes at different development tissues were also identified. Most members of TaGSTU30 and TaTPS1 genes shared similar patterns of exon/intron structures, including intron phase, intron number, and exon length. Drought responsive orthologous genes were also identified in recently released reference genomic data of wheat (available on Ensembl Plants), which were previously identified in rice and Arabidopsis plants. The results of the study would permit a better understanding of the structure and advancement of the genes and the encoded proteins and also provide information for the exploitation of variability for the engineering of these genes.